Not so golden - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The publicity early in 2001 about Golden Rice , with its genetically added Vitamin A promising to reduce child blindness, has revived interest in so-called edible vaccines . Golden Rice, which contains a gene added from the daffodil...